2003
DOI: 10.1007/s00066-003-1082-4
|View full text |Cite
|
Sign up to set email alerts
|

Sucralfate versus Mesalazine versus Hydrocortisone in the Prevention of Acute Radiation Proctitis during Conformal Radiotherapy for Prostate Carcinoma

Abstract: Topical mesalazine is contraindicated during radiotherapy. Hydrocortisone enema is not superior to sucralfate in preventing acute rectal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Numerous studies have been performed to prevent acute and late rectal toxicity, but till now, medical prevention of proctitis remains unsatisfactory [2,3,15,20,22,30,33,36,37,39]. In animal models, systematically as well as topically administered misoprostol has been shown to protect against radiation-induced mucosa injury of the small bowel [5, 9-12, 14, 31].…”
Section: Medical Prevention Of Radiationinduced Late Rectal Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been performed to prevent acute and late rectal toxicity, but till now, medical prevention of proctitis remains unsatisfactory [2,3,15,20,22,30,33,36,37,39]. In animal models, systematically as well as topically administered misoprostol has been shown to protect against radiation-induced mucosa injury of the small bowel [5, 9-12, 14, 31].…”
Section: Medical Prevention Of Radiationinduced Late Rectal Toxicitymentioning
confidence: 99%
“…Though an association between acute and late toxicity remains controversial, some previously published reports discussed that there might be a correlation between both [34,42,44]. Numerous different drugs for the prevention and treatment of radiation-induced rectal toxicity are available [2,3,15,20,22,30,33,36,37,39], but effective medicals for both treatment and prevention remain unsatisfactory [2,3,15,20,22,25,27,30,33,36,37,39]. One randomized study indicated that misoprostol suppositories might prevent acute and late radiation-induced proctitis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Auch in unserem Patientengut litten 38% unter Nebenwirkungen Grad III und IV (nach WHO). Häufigste Nebenwirkung und Gegenstand intensivster Untersuchungen [24] ist die Proktitis. Auch bei unseren Patienten stellte die mit einer Proktitis assoziierte Diarrhö die wichtigste Nebenwirkung dar.…”
Section: Diskussionunclassified
“…The normal tissues most relevent to radiation toxicity typically contain epithelial cells with high rates of turnover including the lining of the gastrointestinal tract and the skin. Existing radiation protectors including the FDA-approved amifostine (Brizel, 2007), sucralfate (Hovdenak et al, 2005), and mesalazine (Sanguineti et al, 2003) are of limited utility in protecting these normal tissues against radiation effects primarily due to their own toxicity.…”
Section: Introductionmentioning
confidence: 99%